Characterization and Duodenal Transcriptome Analysis of Chinese Beef Cattle With Divergent Feed Efficiency Using RNA-Seq - Yang, Chaoyun; Han, Liyun; Li, Peng; Ding, Yanling; Zhu, Yun; Huang, Zengwen; Dan, Xingang; Shi, Yuangang; Kang, Xiaolong (Frontiers in Genetics, 2021)
Residual feed intake (RFI) is an important measure of feed efficiency for agricultural animals. Factors associated with cattle RFI include physiology, dietary factors, and the environment. However, a clear genetic mechanism underlying cattle RFI variations in duodenal tissue is currently unavailable. The present study aimed to identify the key genes and functional pathways contributing to variance in cattle RFI phenotypes using RNA sequencing (RNA-seq). Ten bulls with extreme high or low RFIs were selected for detecting DEGs by RNA-seq, followed by conducting GO, KEGG enrichment, protein-protein interaction (PPI) and co-expression network (WGCNA) analysis. A total 380 differentially expressed genes was obtained from high and low RFI groups, including genes related to energy metabolism (ALDOA, HADHB, INPPL1), mitochondrial function (NDUFS1, RFN4, CUL1) and feed intake behavior (CCK). Two key sub-networks and 26 key genes were detected using GO analysis of DEGs and PPI analysis, such as TPM1 and TPM2 which are involved in mitochondrial pathways and protein synthesis. Through WGCNA, a gene network was built, and genes were sorted into 27 modules, among which the blue (r=0.72, P=0.03) and salmon modules (r=-0.87, P=0.002) were most closely related with RFI. DEGs and genes from the main sub-networks and closely related modules were largely involved in metabolism; oxidative phosphorylation; glucagon, ribosome, and N-glycan biosynthesis; and the MAPK and PI3K-Akt signaling pathways. Through WGCNA, five key genes including FN1 and TPM2 that are associated with the biological regulation of oxidative processes and skeletal muscle development were identified. Taken together, our data suggest that the duodenum has specific biological functions in regulating feed intake. Our findings provide broad-scale perspectives for identifying potential pathways and key genes involved in the regulation of feed efficiency in beef cattle.